2006
DOI: 10.1897/05-112r.1
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan in a North Texas wastewater treatment plant and the influent and effluent of an experimental constructed wetland

Abstract: The antimicrobial triclosan was analyzed in unfiltered samples from influent, effluent, and receiving stream and before and after a pilot-scale constructed wetland at a North Texas municipal wastewater treatment plant. Triclosan concentrations were reduced by 97 to 99% by the activated sludge treatment plant. Effluent concentrations were further reduced by passage through the constructed wetland, but receiving stream concentrations were not statistically significantly different from effluent concentrations. Ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 21 publications
(58 reference statements)
0
38
0
2
Order By: Relevance
“…For the emission of TCS to the receiving environment, the pathways into the water and soil compartments were considered. Since sewage is the main carrier for TCS, the TCS incorporated in the sewage from urban population can be mostly removed in WWTPs before it enters into surface water (Halden 2014;Halden and Paull 2005;Lozano et al 2013;Waltman et al 2006). But, for the TCS in sewage from rural population, it is assumed that the sewage is directly discharged into the receiving environment without treatment based on the report by Ministry of Environmental Protection of China (GOSC 2012).…”
Section: Emission Estimationmentioning
confidence: 99%
“…For the emission of TCS to the receiving environment, the pathways into the water and soil compartments were considered. Since sewage is the main carrier for TCS, the TCS incorporated in the sewage from urban population can be mostly removed in WWTPs before it enters into surface water (Halden 2014;Halden and Paull 2005;Lozano et al 2013;Waltman et al 2006). But, for the TCS in sewage from rural population, it is assumed that the sewage is directly discharged into the receiving environment without treatment based on the report by Ministry of Environmental Protection of China (GOSC 2012).…”
Section: Emission Estimationmentioning
confidence: 99%
“…However, in sewage water, the recovery rate for all compounds except acetaminophen was about half at 42 ± 9%. Recovery rates have also been low in most previous studies 1,6,7) on PPCPs concentrations in sewage. This can be explained by matrix suppression.…”
Section: Methodsmentioning
confidence: 82%
“…Previous studies have reported the matrix suppression with the analysis of PPCPs in water samples. 1,6,7) In addition, this is thought to be because sewage water contains various contaminants, and most PPCPs are amphoteric compounds, but details are unknown. However, in the present study, it was necessary to ascertain the concentration order of PPCPs in sewage water, and as a result, instead of measuring the recovery rate for each compound, the concentration of each compound was calculated by the absolute calibration curve method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triclosan (5-chloro-2-[2,4-dichlorophenoxy]-phenol; TCS) and triclocarban (3,4,4 0 -trichlorocarbanilide; TCC) are commonly used as bactericidal additives in various personal care products (PCPs), such as shampoo, toilet soap and toothpaste. 1,2 The contents of TCS and TCC in these products usually range from 0.1-0.3% and 0.5-5% (w/w), respectively.…”
Section: Introductionmentioning
confidence: 99%